Economic constraint and self-tax relief: effects on tax compliance and tax evasion - Thineswary Mani Ras,; Noorsakinah Abdul Wahab,; Maizatulakma Abdullah,; Siti Fatimah Abdul Rashid,; Norul Syuhada Abu Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper investigates the impact of self-tax relief on tax compliance and tax evasion among individual taxpayers as well as the influence of economic constraints on these relationships. This study employs a survey methodology that specifically targets individual taxpayers in Malaysia. Leveraging on the theory of planned behaviour, the findings reveal that self-tax relief has a positive effect on tax compliance and a negative effect on tax evasion. The findings also reveal that economic constraint moderates the relationship between self-tax relief with tax compliance and tax evasion. This study makes significant contribution to the literature through addressing the role of economic factors in determining the behaviour of individual taxpayers. Despite ongoing discussions on how economic constraints influence tax compliance and tax evasion, empirical evidence remains limited. More specifically, this study addresses a research gap focusing on the impact of current economic constraints on the relationship between self-tax relief, tax compliance, and evasion. The study provides implications for policymakers on the need to account for economic factors and tax policy. It specifically suggests improvements in the tax structure such as continuous assessment of the value of self-tax relief that could encourage tax compliance and mitigate evasion.